Geographical association of biodiversity with cancer and cardiovascular mortality rates: analysis of 39 distinct conditions - Xu, Qiaochu; Qu, Bingjie; Li, Li; Chen, Ying (Frontiers in Public Health, 2024)
Background: Biodiversity has been recognized as a positive contributor to human health and wellbeing. Cardiovascular disease and cancer, two most significant global health burdens, understanding their relationship with biodiversity forms the essential step towards promoting the biodiversity conservation and human health. Methods: The species richness of birds is a common indicator of biodiversity, given their vast numbers, distinctive distribution, and acute sensitivity to the environmental disturbances. This ecological study utilized avian observation data derived from eBird database, human health data from the International Health Metrics and Evaluation, as well as the county-level statistics, including population characteristics, socio-economics, healthcare service, residential environment, and geographic and climatic characteristics in 2014. We aimed to extensively explore the individual associations between biodiversity (i.e., avian species richness) and age-standardized cause-specific mortalities for different types of cancers (29 conditions) and cardiovascular diseases (10 conditions) across the USA. Results: Our multiple regression analyses that adjusted for a variety of socio-demographic and geographical factors showed that increased rarefied species richness of birds was associated with reduced mortality rates for three of the five most common cancers, i.e., tracheal, bronchus and lung cancer, breast cancer (in females only) and colon and rectal cancer. For cardiovascular conditions, a similar relationship was observed for ischemic heart disease and cerebrovascular disease-the two most frequent causes of mortality. This study provided extended details regarding the beneficial effects of biodiversity to human health.